2017
DOI: 10.1177/0265407517703492
|View full text |Cite
|
Sign up to set email alerts
|

Great expectations

Abstract: Expectations for one’s romantic relationship, and the extent to which these expectations are actually met, are important predictors of relationship outcomes. Themes of romanticism (e.g., idealism, soul mates, love at first sight) emerge from our romantic socialization. But what happens when romantic relationships fall short of these ideals and expectations are unmet? The current study examined the association among unmet romantic expectations and relationship outcomes using an investment model framework. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
(81 reference statements)
0
11
0
2
Order By: Relevance
“…For example, recent studies have investigated additional proximal predictors on commitment and alternative versions of the Investment Model predictors, such as perceptions of one's partner's investments (Joel, Gordon, Impett, MacDonald, & Keltner, 2013), the counterfactual potency of forgone alternatives (Petrocelli, Kammrath, Brinton, Uy, & Cowens, 2015), forecasted future relationship satisfaction (Lemay Jr, 2016) and future plans as another form of investment (Tan & Agnew, 2016), and subjective norms (Etcheverry & Agnew, 2004). Research has also investigated the role of more distal predictors of commitment, such as anxious and avoidant attachment orientations, (Etcheverry, Le, Wu, & Wei, 2013) and unmet ideal expectations (Vannier & O'Sullivan, 2017), which influence commitment indirectly via the three Investment Model antecedents. Recent research has also gone beyond focusing on demographic moderators to investigate potential psychological moderators of the relationships in the model, such as one's self-determined relationship motivation (Hadden, Knee, DiBello, & Rodriguez, 2015).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…For example, recent studies have investigated additional proximal predictors on commitment and alternative versions of the Investment Model predictors, such as perceptions of one's partner's investments (Joel, Gordon, Impett, MacDonald, & Keltner, 2013), the counterfactual potency of forgone alternatives (Petrocelli, Kammrath, Brinton, Uy, & Cowens, 2015), forecasted future relationship satisfaction (Lemay Jr, 2016) and future plans as another form of investment (Tan & Agnew, 2016), and subjective norms (Etcheverry & Agnew, 2004). Research has also investigated the role of more distal predictors of commitment, such as anxious and avoidant attachment orientations, (Etcheverry, Le, Wu, & Wei, 2013) and unmet ideal expectations (Vannier & O'Sullivan, 2017), which influence commitment indirectly via the three Investment Model antecedents. Recent research has also gone beyond focusing on demographic moderators to investigate potential psychological moderators of the relationships in the model, such as one's self-determined relationship motivation (Hadden, Knee, DiBello, & Rodriguez, 2015).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Health promoting cognitions have been related to growth in relationships, communication, expressing love, and problem solving (Sullivan & Schwebel, 1995). Although prior attempts to organize individuals' relational cognitions have focused on the positive and negative relationship outcomes among heterosexual populations (Holt et al, 2016;Meier & Allen, 2009;Vannier & O'Sullivan, 2018), research examining the components that inform these associations has lacked within the sexual and gender minority literature. In our study, we found evidence to indicate that many of the relational features focused on health promoting cognitions.…”
Section: Discussionmentioning
confidence: 99%
“…cognition, dating, factor analysis, relationships, sexual minority well-being, and are associated with lower relationship satisfaction, commitment, and investment (Soller, 2014;Vannier & O'Sullivan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…La costumbre o ru na, en cambio puede representar un indicador de que las inversiones que se han hecho a la relación son irrecuperables, en este caso las mujeres pueden percibir una mayor inversión de su parte debido a los hijos, la historia y el empo compar dos, así como los recursos emocionales inver dos -que culturalmente son mucho más constantes e intensos en el sexo femenino-, por lo que puede presentarse una mayor resistencia a dejar la relación incluso si esta fuera insa sfactoria (Rusbult et al, 2006). Para la cuarta pregunta ¿Qué debemos pensar para permanecer con nuestra pareja?, se iden ficaron cuatro categorías tanto para adolescente como adultos: que nos amamos, respetar a mi pareja, que estamos bien con la pareja, y que con o en mi pareja, las categorías anteriores reflejan el anhelo y deseo por tener una relación posi va, como una forma de asegurar el éxito de la relación (Retana Franco & Sánchez Aragón, 2006;Sánchez Aragón, 2009), siguiendo esta línea de pensamiento estas dimensiones también se asocian con el constructo de estabilidad, que está estrechamente relacionado con el de permanencia, ya que hace referencia a la congruencia de las expecta vas de la pareja con lo que se vive en la relación (Swann & Giuliano, 1987;Vannier & O'Sullivan, 2017). Adicionalmente, los adultos mencionaron que se debe pensar en que se ene un compromiso, esta dimensión esta ma zada por caracterís cas ligadas al rol de género culturalmente aceptado.…”
Section: Discussionunclassified